Kinematics of balance controls in people with chronic ankle instability during unilateral stance on a moving platform - Xiaohan Xu; Joanna Bowtell; Daniel T. P. Fong; William R. Young; Genevieve K. R. Williams (Scientific Reports)
Abstract Balance control deficits resulting from ankle sprains are central to chronic ankle instability (CAI) and its persistent symptoms. This study aimed to identify differences in balance control between individuals with CAI and healthy controls (HC) using challenging single-leg balance tasks. Twenty-three CAI and 23 HC participants performed balance tasks on a force plate that either remained static or moved mediolaterally. Force and kinematic data were recorded to measure balance and joint movements. The CAI group showed significantly shorter time-to-boundary during static conditions but no significant differences during moving conditions compared to HC. During moving conditions, CAIs exhibited greater proximal compensations, with greater range of motion and higher angular velocity in the knee, hip, and torso. while no significant differences were observed in these parameters during static conditions. Principal component analysis indicated specific kinetic chain in CAI during one-leg balance under both static and moving conditions compared to HC. These findings suggest an altered movement strategy in CAI, that ankle injuries impair the ability to stabilize both distal and proximal joints, and an altered kinetic chain from ankle to torso. Rehabilitation programs for CAI might benefit from considering the integration of the entire kinetic chain, addressing both distal and proximal joint dynamics to support effective recovery and prevent secondary injuries.